The Association of Helicobacter pylori Infection and Virulence Factors in Gastric Cancer in Thi-Qar, Iraq - Qasim, Maytham T.; Mohammed, Zainab I. (Asian Pacific Journal of Cancer Biology, 2024)
Background: The significance of Helicobacter pylori (H. pylori) infection in developing gastric cancer has been increasingly recognized. However, a noticeable gap exists in the literature regarding the prevalence of key virulence factors, particularly in Iraq. Therefore, Our study aimed to investigate the prevalence of H. pylori infection and the presence of virulence factors, namely the CagA and VacA genes, in gastric cancer patients. Methods: A case-control study was conducted on 45 gastric cancer patients (38 males and 7 females) from September 2020 to February 2021. During routine endoscopic procedures, gastric biopsy specimens were collected from the tumour and adjacent non-tumour tissues. The presence of H. pylori was detected using quantitative real-time PCR, and the virulence factors CagA and vacA were identified using specific primers. Results: H. pylori infection was detected in a significant 85% (38/45) of the patients, with a higher prevalence in males 89.5% (34/38) compared to females 10.5% (4/38) (P=0.021) (Chi-square test). No significant age-related differences were observed. The CagA gene was present in a substantial 58.8% (22/38) of H. pylori-positive patients, predominantly in tumor tissues at 81.81% (18/22), while the vacA gene was found in only one patient. These results underscore the importance of our research in understanding the prevalence of H. pylori infection and the presence of virulence factors in gastric cancer patients. Conclusion: The high prevalence of H. pylori infection and the significant presence of the CagA virulence factor in tumour tissues underscore the bacterium’s role and risk factors in gastric carcinogenesis in Thi-Qar, Iraq.